„Śmiechem poza siebie wybiegać”. O szczególnym artefakcie maladyczno-geloterapeutycznym - Samborska-Kukuć, Dorota (Er(r)go. Teoria - Literatura - Kultura, 2023)
In the 20th century, tuberculosis was already perceived as a democratic disease. An overview of tuberculosis became different and less serious. Seven-volumed press ephemerid from the interwar period, that is, Prątka Jednodniówka (Bystra Śląska) is one of the examples. This journal is gelotherapeutic. Introducing satirical, journalistic, literary and graphic genres, it used some sophisticated rhetorical and metaphorical devices to familiarize tuberculosis and made an attempt of a laughter therapy. A sense of community associated with the undertaking, placing the subject in the health resort reality and undertaking medical issues in a humorous manner: the aim of all these factors was to show the life in the sanatorium as well as tuberculosis itself in the crooked mirror of a satire.